A data‐driven analysis for fatigue failure mode identification in load‐carrying fillet welded joint with mechanical data augmentation. Issue 11 (16th August 2022) - Zhao, Ziqi; Zhang, Tairui; Song, Wei; Jiang, Wenchun; Wang, Ping; Xing, Shizhu; Pei, Xianjun
Abstract: Weld toe and weld root failures dominate the fatigue failures of the load‐carrying cruciform fillet welded joints. Compared to weld toe failure, the weld root failure is strongly affected by its inherent weld quality and throat size, which is more unpredictable and should be eliminated. This work proposes a weld sizing criterion in terms of two weld leg sizes and weld penetration to avoid root failure. The criterion is obtained by a data‐driven approach with the help of the mechanical‐directed data augmentation technique. The traction‐stress‐based method is applied for the data augmentation to identify the fatigue failure mode, which is statistically tested against 372 experimentally obtained fatigue data.